Upaya Meningkatkan Kemampuan Mengingat Huruf Pada Anak Usia 4-5 Tahun Melalui Metode Bernyanyi di PAUD At-Taufiq - Hindun, Siti; Zultiar, Indra; Munajat, Asep (PT. Alahyan Publisher Sukabumi, 2025)
This study aims to improve letter recall abilities in children aged 4-5 years through the singing method at PAUD AT-TAUFIQ. Using Classroom Action Research (CAR) method in two cycles, this study involved 19 children from Group A. The results showed significant improvement, where the